Study on Microclimate Characteristics and Vertical Variation of Potential Evapotranspiration of the Robinia pseudoacacia Forest in the Loess Plateau of China - Jianjun Zhang; Baoni Guo; Qun’ou Jiang; Hao Ru; Zhen Wang (Advances in Meteorology)
With the water and soil conservation forests of Robinia pseudoacacia in the Malian beach of Hongqi farm, Ji County, Shanxi province, as the research object, this study estimated the potential evapotranspiration in the open space outside the forest and at the heights of 3 m, 6 m, and 10 m in the forests with the climate data during 2011-2012 and the upgraded Penman-Monteith formula; then, this study explored the microclimate characteristics inside and outside the Robinia pseudoacacia forest and thereafter revealed the vertical variation rules of potential evapotranspiration of Robinia pseudoacacia. The results indicate that the air temperature, relative humidity, wind speed, and potential evapotranspiration at different heights above the ground surface showed similar changing trends, but with some variation during different periods. In addition, the weather also had impacts on the potential evapotranspiration. In April, July, and October, the change of potential evapotranspiration of the Robinia pseudoacacia forests showed a bimodal curve in the sunny days and rainy days, while it showed a single-peak curve with quite small fluctuation in the rainy days. However, it showed a single-peak pattern even in the sunny days in January, and it showed no fluctuation in the snowy days in January.